2022
DOI: 10.1111/geb.13534
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and fishing are pulling the functional diversity of the world's largest marine fisheries to opposite extremes

Abstract: Aim: Marine biodiversity is increasingly threatened by overfishing and climate change, but it is still unclear how these drivers have shaped the functional diversity (FD) of marine fish. Here, we explore how the FD of commercial marine fish communities responds to climate change and fishing pressure.Major taxa studied: Marine fish.Location: China Seas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 110 publications
0
21
0
Order By: Relevance
“…biodiversity loss continues at regional and global scales in diverse ecosystems (Vitousek et al, 1997;Cardinale et al, 2006;Maclean and Wilson, 2011;Worm and Tittensor, 2011;Mouillot et al, 2013). As a critical part of biodiversity, functional diversity indices have been increasingly applied to fish communities to explore the connection between biodiversity and ecosystem function, indicate the community structure changes, and assess the effect of multiple pressures (Villeǵer et al, 2010;Mouillot et al, 2013;Stuart-Smith et al, 2013;Belley and Snelgrove, 2016;Villeǵer et al, 2017;Rolim et al, 2022;Zhao et al, 2022). However, only a few studies so far report the functional diversity of marine fish communities.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…biodiversity loss continues at regional and global scales in diverse ecosystems (Vitousek et al, 1997;Cardinale et al, 2006;Maclean and Wilson, 2011;Worm and Tittensor, 2011;Mouillot et al, 2013). As a critical part of biodiversity, functional diversity indices have been increasingly applied to fish communities to explore the connection between biodiversity and ecosystem function, indicate the community structure changes, and assess the effect of multiple pressures (Villeǵer et al, 2010;Mouillot et al, 2013;Stuart-Smith et al, 2013;Belley and Snelgrove, 2016;Villeǵer et al, 2017;Rolim et al, 2022;Zhao et al, 2022). However, only a few studies so far report the functional diversity of marine fish communities.…”
mentioning
confidence: 99%
“…Thus, China's sustainable marine capture fishery industry is critical to the global seafood supply, food security, and seafood trade (Smith et al, 2010;Blomeyer et al, 2012;Su et al, 2020). Zhao et al (2022) recently used China's reported marine catch data and a comprehensive set of functional traits to explore how the functional diversity of commercial fish communities responds to climate change and changes in fishing pressure. They showed that climate warming and fishing significantly and oppositely affect the functional diversity (i.e.,FEve and FDiv), partly causing functional diversity fluctuations in China's seas.…”
mentioning
confidence: 99%
See 3 more Smart Citations